BIOCHEMICAL ESTIMATION OF PRIMARY METABOLITES IN OCIMUM TENUIFLORUM - ARCHANA SHARMA; ANJU MEENA; RISHI KESH MEENA (The Bioscan, 2011)
Ocimum tenuiflorum is an important medicinal herb belonging to family Lamiaceae. It is commonly known as ‘Shyama tulsi’. In the present investigation, various in vivo plant parts (leaves, stem and root) and in vitro (callus)of ocimum tenuiflorum was carried out for biochemical estimation of primary metabolites viz. total soluble sugar, starch, lipid, protein and phenol. The plant parts varied in composition of their primary metabolites.Results showed that the maximum content of total soluble sugar (3.5±0.08 mg/gfw), lipid (2.6±011 mg/gfw), protein (3.6±0.65 mg/gfw) and phenol (1.8±0.456 mg/gfw) and maximum starch found in root (2.1±.014 mg/gfw).